Designing artificial environments for preterm infants based on circadian studies on pregnant uterus - Watanabe, Shimpei; Akiyama, Shizuko; Hanita, Takushi; Li, Heng; Nakagawa, Machiko; Kaneshi, Yousuke; Ohta, Hidenobu; filter study group, Japan RED (Frontiers in Endocrinology, 2013)
Using uterine explants from Per1::Luc rats and in situ hybridization, we recently reported that the circadian property of the molecular clock in the uterus and placenta is stably maintained from non-pregnancy, right through to the end stage of pregnancy under regular light-dark cycles. Despite long-lasting increases in progesterone during gestation and an increase in estrogen before delivery, the uterus keeps a stable Per1::Luc rhythm throughout the pregnancy. The study suggests the importance of stable circadian environments for fetuses to achieve sound physiology and intrauterine development. This idea is also supported by epidemiological and rodent studies, in which pregnant females exposed to repeated shifting of the light-dark cycles have increased rates of reproductive abnormalities and adverse pregnancy outcomes. Leading from this, we introduced artificial circadian environments with controlled lighting conditions to human preterm infants by developing and utilizing a specific light filter which takes advantage of the unique characteristics of infants’ developing visual photoreceptors. In spite of growing evidence of the physiological benefits of nighttime exposure to darkness for infant development, many Japanese Neonatal Intensive Care Units (NICUs) still prefer to maintain constant light in preparation for any possible emergencies concerning infants in incubators. To protect infants from the negative effects of constant light on their development in the NICU, we have developed a new device similar to a magic mirror, by which preterm infants can be shielded from exposure to their visible wavelengths of light even in the constant light conditions of the NICU while simultaneously allowing medical care staff to visually monitor preterm infants adequately. The device leads to significantly increased infant activity during daytime than during night time and better weight gains.